2004
DOI: 10.1038/sj.bjc.6601999
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of specialisation in the management of pancreatic cancer: results of a Scottish population-based study

Abstract: Pancreatic cancer is associated with a very poor prognosis; however, in selected patients, resection may improve survival. Several recent reports have demonstrated that concentration of treatment activity for patients with pancreatic cancer has resulted in improved outcomes. The aim of this study was to ascertain if there was any evidence of benefit for specialised care of patients with pancreatic cancer in Scotland. Records of patients diagnosed with pancreatic cancer during the period 1993 -1997 were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…The achievement of an R0 resection margin is one of the most important prognostic factors in the treatment of pancreatic head tumours, thus the current results suggest that patients treated in high‐volume hospitals may have a better long‐term survival in patients with pancreatic head tumours than those treated in low‐volume hospitals. This is confirmed by two recent studies that showed that centralization improves the 2‐ and 3‐year survival after surgery for pancreatic head tumours.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The achievement of an R0 resection margin is one of the most important prognostic factors in the treatment of pancreatic head tumours, thus the current results suggest that patients treated in high‐volume hospitals may have a better long‐term survival in patients with pancreatic head tumours than those treated in low‐volume hospitals. This is confirmed by two recent studies that showed that centralization improves the 2‐ and 3‐year survival after surgery for pancreatic head tumours.…”
Section: Discussionsupporting
confidence: 73%
“…2 A number of studies have outlined the relationship between hospital volume, post-operative mortality, and survival for patients undergoing surgery for pancreatic and peri-ampullary neoplasms. [3][4][5][6][7][8][9][10][11][12] It has been postulated that both short-and long-term improvements in the outcome of a pancreatic resection are mainly as a result of improvements in the quality of HPB surgery and peri-operative care. 7 In patients with pancreatic ductal adenocarcinoma (PDAC), the ratio of nodal involvement and, to a somewhat lesser extent, the negative resection margin (R0) are the most important prognostic factors for long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…77 Although these are indirect indicators of quality of care, they have been shown to be important in determining outcome. [78][79][80] Simple measures such as delay in diagnosis, or delay in receiving appropriate treatment, provide information on equity and access, as well as potentially infl uencing outcome. 81 Auditing the nature of the diagnostic and therapeutic procedures actually performed provides a more direct indication of the quality of care; if the focus is effectiveness of care, then the choice of indicators should be known to have an effect on its outcome.…”
Section: Clinical Carementioning
confidence: 99%
“…There have also been improvements in both adjuvant and palliative chemotherapy. Radiotherapy [4][5][6] and centralized surgery have also been proposed [7,8]. The repercussion of these changes at the population level is not known.…”
Section: Introductionmentioning
confidence: 97%